2012
DOI: 10.4314/ijbcs.v5i4.29
|View full text |Cite
|
Sign up to set email alerts
|

Influence of antioxidant vitamins supplementation on blood glucose levels and body wastages of alloxan-induced diabetic rats

Abstract: There is increasing evidence that in certain pathology states, the increased production and/or ineffective scavenging of reactive oxygen species (ROS) may play a critical role. Therefore, it seems reasonable that antioxidants can play an important role in the management of these diseases. In the current study, antioxidant vitamins A, C and E were supplemented in alloxan-induced diabetic rats for a period of 28 days. Blood glucose level was assayed by the method of Trinder (1969) and digital bench weigh balance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…When plant extracts was received, the levels of urea, creatine, and uric acid significantly decreased (P≤ 0.05), easing the impaired effect. The accelerated breakdown of liver and plasma proteins that occurs with gluconeogenesis associated with hyperglycemia may be to blame for the rise in urea levels seen in diabetes [31].…”
Section: Effect Of Crude Aqueous Extract Of V Subterrenea Leaf Nut St...mentioning
confidence: 99%
See 1 more Smart Citation
“…When plant extracts was received, the levels of urea, creatine, and uric acid significantly decreased (P≤ 0.05), easing the impaired effect. The accelerated breakdown of liver and plasma proteins that occurs with gluconeogenesis associated with hyperglycemia may be to blame for the rise in urea levels seen in diabetes [31].…”
Section: Effect Of Crude Aqueous Extract Of V Subterrenea Leaf Nut St...mentioning
confidence: 99%
“…Studies have also shown that patients with diabetes exhibit changes in their hematological indices, Patients with diabetes experience persistent high blood sugar levels, which can lead to the glycation of various proteins involved in clotting mechanisms, such as hemoglobin, prothrombin, and fibrinogen, in addition to red blood cells [31]. This alteration in hematology indices is a consequence of the glycation process [32].…”
Section: Effect Of Crude Aqueous Extract Of V Subterrenea Leaf Nut St...mentioning
confidence: 99%
“…About 5 mls of blood sample was obtained through cardiac puncture and divided into fluoride oxalate and lithium heparin anti-coagulated containers. Humane procedure was used as adopted [13]. Blood samples were centrifuged at 3000 rpm for five (5) minutes and plasma obtained was used for analysis.…”
Section: Sample Collectionmentioning
confidence: 99%
“…This leads to the exhaustion of beta cells and, upon prolonged hyperglycemia, their apoptosis, causing progression of the disease [13]. Accordingly, the secretion of insulin is strictly controlled by glucose, other hormones, and the autonomic nervous system [14]. Glycated haemoglobin is an indirect measure of average blood glucose levels [15].…”
Section: Introductionmentioning
confidence: 99%